Chimeric Antigen Receptor T Cell Therapy Management and Safety: A Practical Tool From a Multidisciplinary Team Perspective - Marzal-Alfaro, María Belen; Escudero-Vilaplana, Vicente; Revuelta-Herrero, Jose Luis; Collado-Borrell, Roberto; Herranz-Alonso, Ana; Sanjurjo-Saez, Maria (Frontiers in Oncology, 2021)
Purpose: The use process for chimeric antigen receptor T (CAR-T) cell drugs is complex and has been associated with a number of potentially severe complications, which requires management by a multidisciplinary team. Pharmacists are a key element in the team and have roles and responsibilities. Our objective was to develop a structured and practical guide that supports hospital pharmacist responsibilities and defines specific activities in a CAR-T cell therapy program. Methods: A literature review was performed and the recommendations related to pharmacy practice in CAR-T therapy programs were analyzed. A multidisciplinary team was assembled and meetings were held to address the key tasks in the CAR-T cells management process and to create the guide, based on national and international recommendations and in expert’s opinions. Results: The multidisciplinary team defined the following key tasks and issued recommendations to improve patient safety, treatment efficacy and quality: patient selection and evaluation, CAR-T cell drug order to manufacturer, apheresis and material shipment, reception of CAR-T cell drug and storing, CAR-T cell drug prescription and pharmacy verification, CAR-T cell drug thawing and dispensing, CAR-T cell drug administration, patient education, pharmacovigilance and monitoring, outcomes record and evaluation and treatment of waste. In each task the pharmacist’s role and how it can improve patient care is defined. A checklist was created to guarantee the compliance of standard operating procedures approved in the institution to manage CAR-T cell therapy and as a tool to collect required data for outcomes record and evaluation. Conclusion: This article provides a consensus set of safety recommendations regarding CAR-T therapy management in clinical practice, easily implementable by other institutions. The guide identifies key steps were the involvement of hospital pharmacists would improve the safety and quality of the process and is a support guide to standardize hospital pharmacists’ responsibilities within the multidisciplinary team.